DEVELOPING DESCRIPTIVE TEXT TEACHING MATERIAL BASED ON LOCAL WISDOM FOR STUDENTS OF SMPN 2 SETIA JANJI - Fitri Kumala Sari; Asnawi Asnawi; Sarianto Sarianto (SOSIOEDUKASI, 2026)
This study aims to develop English descriptive text teaching materials based on the local wisdom of Asahan Regency using the Problem-Based Learning (PBL) model and to examine the feasibility of the materials as well as students’ responses toward their implementation. The study is motivated by students’ low achievement and limited interest in learning descriptive texts, which are largely caused by the use of generic teaching materials that are not contextualized to students’ real-life experiences. This research employed a Research and Development (R&D) design consisting of needs analysis, material design, product development, expert validation, and limited field testing at SMP Negeri 2 Setia Janji. Data were collected through classroom observations, questionnaires, and interviews, and were analyzed using both qualitative and quantitative descriptive techniques. The findings indicate that the developed teaching materials were considered valid and feasible by material and media experts. The results of the field testing also reveal an improvement in students’ engagement, learning motivation, and understanding of the structure and vocabulary of descriptive texts. Integrating local wisdom within the PBL framework enables students to connect language learning with their cultural and environmental contexts. Therefore, the developed materials are effective as contextual and meaningful English learning resources that support the development of 21st-century skills and strengthen the Pancasila Student Profile.